2020
DOI: 10.1101/2020.04.07.028837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic evidence for a polymicrobial signature of sepsis

Abstract: 12Sepsis is defined as a life-threatening organ dysfunction arising from a dysregulated host response to 13 infection. The last two decades have seen significant progress in our understanding of the host component 14 of sepsis. However, detailed study of the composition of the microbial community present in sepsis, or 15 indeed, the finer characterisation of this community as a predictive tool to identify sepsis cases, has only 16 received limited attention. The microbial component of sepsis has been att… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In fact, variable microbial DNA pro les in blood have been used to delineate health and disease states. This has most prominently been shown for sepsis [53][54][55][56][57]65 , where the presence of viable microbes is expected, but also for cancer 30 , periodontal disease 51 , and chronic kidney disease 66 , which are unrelated to bloodstream infections. These studies highlight the promise of metagenomic sequencing of blood for developing diagnostic, prognostic, or therapeutic tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, variable microbial DNA pro les in blood have been used to delineate health and disease states. This has most prominently been shown for sepsis [53][54][55][56][57]65 , where the presence of viable microbes is expected, but also for cancer 30 , periodontal disease 51 , and chronic kidney disease 66 , which are unrelated to bloodstream infections. These studies highlight the promise of metagenomic sequencing of blood for developing diagnostic, prognostic, or therapeutic tools.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence estimates provided in this study are contingent on the sensitivity of detecting microbes through sequencing. Previous studies have shown that untargeted shotgun sequencing is highly sensitive for the detection of microbes in blood at a total sequencing depth of 20-30 million reads per sample [53][54][55] , perhaps even more so than culture-based methods 56,57 . In contrast, a median of 373 million reads was generated per sample for our sequencing libraries, suggesting that our methods do not lack sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, variable microbial DNA profiles in blood have been used to delineate health and disease states. This has most prominently been shown for sepsis 35,[54][55][56][57]65 , where the presence of viable microbes is expected, but also for cancer 30 , periodontal disease 52 , and chronic kidney disease 66 , which are unrelated to bloodstream infections. These studies highlight the promise of metagenomic sequencing of blood for developing diagnostic, prognostic, or therapeutic tools.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence estimates provided in this study are contingent on the sensitivity of detecting microbes through sequencing. Previous studies have shown that untargeted shotgun sequencing is highly sensitive for the detection of microbes in blood at a total sequencing depth of 20-30 million reads per sample 35,54,55 , perhaps even more so than culture-based methods 56,57 . In contrast, a median of 373 million reads was generated per sample for our sequencing libraries, suggesting that our methods do not lack sensitivity.…”
Section: Discussionmentioning
confidence: 99%